Unraveling the crime-place connection, Volume 22
1 online resource (299 pages)
Keywords: "Unraveling the Crime-Place Connection examines how places enhance our understanding of crime and its control in a new light. While there has been much work in this area that has a policy focus, few have examined the underlying theories that inform this work. Theory has played a secondary role in the "criminology of place," and this volume brings it to the forefront of scholarly concerns. Each section and its chapters illuminate cutting-edge ideas in the etiology and control of crime at place, beginning with an introductory Section I. Crime is often concentrated in very small geographies, and Section II emphasizes the importance of capturing the dynamic nature of places in order to understand crime clustering. Section III offers integrative theories on the varying contextual arrangements of places and link theories of places to other theories of individuals, neighborhoods, and other social contexts. In Section IV, theorists ask how the actions of place owners facilitate or control crime, and what policies governments can institute to regulate place management, while Section V describes how considerations of place can have the potential to transform the way criminal justice agencies address crime.This volume will be of interest to criminologists worldwide, and has potential for some adoptions in graduate-level or advanced undergraduate courses on environmental criminology or crime prevention."--Provided by publisher.